Upaya Peningkatan Literasi Numerasi Masyarakat Desa Tanjung Medan Kecamatan Bilah Barat Kabupaten Labuhanbatu - Mulkan Ritonga; Rahma Muti'ah; Budianto Bangun; Hari Mansah; Dandi Febrian; Syahrol Sulaiman Ritonga (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Human needs related to resource development generally consist of formal resources and information resources. Formal resource development can be obtained from training that is deliberately carried out for the development of human resources themselves. Numerical literacy skills are needs that can be developed using direct socialization and training methods. Direct training and socialization methods in an effort to improve the numeracy literacy skills of village communities are effective and worthy of consideration. The results of this community service activity prove that with the socialization and direct training methods that focus on training activities with calculation material for calculating irregular rectangular land areas, calculating the number of seeds to the land area, calculating the amount of fertilizer for population/seeds and calculating the amount of land and building tax it is proven can increase the numeracy literacy of the village community.